British Association of Dermatologists guidelines for the management of lichen sclerosus, 2018. (1st April 2018) - Lewis, F.M.; Tatnall, F.M.; Velangi, S.S.; Bunker, C.B.; Kumar, A.; Brackenbury, F.; Mohd Mustapa, M.F.; Exton, L.S.; McHenry, P.M.; Leslie, T.A.; Wakelin, S.; Hunasehally, R.Y.P.; et al.
Abstract: Linked Comment: Akel and Fuller. Br J Dermatol 2018; 178 :823–824 . Plain language summary available online